2020
DOI: 10.1074/jbc.ra120.014476
|View full text |Cite
|
Sign up to set email alerts
|

Glycans function as a Golgi export signal to promote the constitutive exocytic trafficking

Abstract: Most proteins in the secretory pathway are glycosylated. However, the role of glycans in membrane trafficking is still unclear. Here, we discovered that transmembrane secretory cargos, such as interleukin 2 receptor α subunit or Tac, transferrin receptor and cluster of differentiation 8a, unexpectedly displayed substantial Golgi localization when their O-glycosylation was compromised. By quantitatively measuring their Golgi residence times, we found that the observed Golgi localization of O-glycan deficient ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…Similar to constitutive secretory cargo such as Tac and VSVG, the Golgi pool of a glycosyltransferase is determined by the net effect of the following three trafficking pathways, as we previously discussed (Fig. 3A) (Sun et al, 2020): (1) the ER-to-Golgi (anterograde), (2) the Golgi-to-ER (retrograde) and (3) the Golgi-to-PM (exocytic) trafficking pathways. ER-to-Golgi transport increases the Golgi pool whereas the Golgi-to-PM and Golgi-to-ER pathways deplete it.…”
Section: Post-golgi St Is Mainly Degraded By Ed Sheddingmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar to constitutive secretory cargo such as Tac and VSVG, the Golgi pool of a glycosyltransferase is determined by the net effect of the following three trafficking pathways, as we previously discussed (Fig. 3A) (Sun et al, 2020): (1) the ER-to-Golgi (anterograde), (2) the Golgi-to-ER (retrograde) and (3) the Golgi-to-PM (exocytic) trafficking pathways. ER-to-Golgi transport increases the Golgi pool whereas the Golgi-to-PM and Golgi-to-ER pathways deplete it.…”
Section: Post-golgi St Is Mainly Degraded By Ed Sheddingmentioning
confidence: 73%
“…Here, using ST as a primary example, we demonstrate that most post-Golgi glycosyltransferases are not retrieved to the Golgi, and they shed their EDs extracellularly. Owing to the lack of the retrieval pathway, we proposed to adopt Golgi residence time (Sun et al, 2020) as a metric for the Golgi retention of glycosyltransferases. By this approach, we assessed quantitatively and systematically the contribution of the NCT, TMD and ED to the Golgi localization of ST. We found that all three regions contribute additively to efficient Golgi retention of ST and that the NCT length of ST plays a negative role.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently measured the Golgi residence time of VSVG to be 12 min. Furthermore, we found that different constitutive transmembrane secretory cargos have distinct Golgi residence times, which are determined by their Golgi export signals, such as the linked glycan, the transmembrane domain, and the cytosolic tail ( Sun et al, 2021 ; Sun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 98%
“…4 C ). The length of time that VSVG pauses at the trans-Golgi is indicated by its Golgi residence time, which can be measured by the half-life of the Golgi fluorescence decay after the release of 20°C block ( Sun et al, 2021 ; Sun et al, 2020 ). We have recently measured the Golgi residence time of VSVG to be 12 min.…”
Section: Resultsmentioning
confidence: 99%
“…The recent identification of new Golgi-localized oncogenes and tumor suppressors encourages the hypothesis that many other molecules of this kind have yet to be identified ( McKinnon and Mellor, 2017 ; Obata et al, 2017 ; Jensch et al, 2018 ; Sun et al, 2020 ). Unfortunately, despite the correlation between Golgi-based signaling and the maintenance of specific tumor phenotypes, a systematic analysis in a broad spectrum of tumors is still missing.…”
Section: Discussionmentioning
confidence: 99%